PERGESERAN PARADIGMA TAFSIR ALA LINGUIS (Studi atas Kitab “Qira’ah Mu’ashirah” Karya Muhammad Syahrur) - John Supriyanto (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2018)
This article attempts to explore one perspective of the knowledge of the Qur'an and interpretation. Muhammad Shahrur ad-Dayyub, a linguist with civil engineering background, offers a new approach to understanding the Qur'an. Syahrur's concept about Qur'an which published in